Preface and Guide - Geoffrion, A. M. (Management Science, 1974)
My objective in assembling this issue was to garner articles that would be of clear and present interest to those who professionally develop or apply mathematical programming techniques. It was not enough for a prospective paper to be competent, original, or even a dazzling display of intellectual prowess. Rather, each paper selected had to satisfy the more difficult criterion of usefully supporting, illuminating, or advancing the current state-of-the-art of applicable mathematical programming.